2011
DOI: 10.1002/maco.200905344
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion protection of stainless steel by separate polypyrrole electrode in acid solutions

Abstract: Galvanic anodic protection (GAP) of stainless steels by doped polypyrrole (PPy) was investigated using chemically synthesized PPy. Separate PPy powderpressed electrodes with different surface areas were prepared. Electrochemical properties of PPy electrodes were studied by open circuit potentials (OCPs) and potentiostatic polarization. PPy powder-pressed electrodes were coupled with 410-stainless steel electrodes in different concentrations of sulfuric acid solutions, 5 M phosphoric acid solution, and industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…16 Moreover, there is still controversy over whether the doped or undoped form of PANI protects steel better. 17,18 For the most part of the studies regarding corrosion protection via conducting polymers, conducting polymers have been used singly, 13,[19][20][21][22] however, in some of the other studies conducting polymers have been used in binaryform as copolymer [23][24][25] or as bilayer coating. [26][27][28] 36 In the present authors' previous work, 37 it was found that the passivation of ZnCo alloy surface was necessary for homogenous polymer film synthesis prior to monomer oxidation and film growth.…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, there is still controversy over whether the doped or undoped form of PANI protects steel better. 17,18 For the most part of the studies regarding corrosion protection via conducting polymers, conducting polymers have been used singly, 13,[19][20][21][22] however, in some of the other studies conducting polymers have been used in binaryform as copolymer [23][24][25] or as bilayer coating. [26][27][28] 36 In the present authors' previous work, 37 it was found that the passivation of ZnCo alloy surface was necessary for homogenous polymer film synthesis prior to monomer oxidation and film growth.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, new generations of environmental friendly coatings, which employed water as their solvent have attracted many attentions of researchers . Because of less solvent of water‐based systems compared to solvent‐based coatings, and the reductions in VOC emissions, the working environment would be improved .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies developed about pitting corrosion are based on polarisation techniques [21][22][23][24]. However, these techniques involve a serial of human interpretation that may lead to poor quality results [25].…”
Section: Introductionmentioning
confidence: 99%